A parameterization strategy for hydrodynamic modelling of a cascade of poorly monitored reservoirs in Brazil. (December 2020) - Soares, Laura Melo Vieira; Calijuri, Maria do Carmo; Silva, Talita Fernanda das Graças; Moraes Novo, Evlyn Marcia Leão de; Cairo, Carolline Tressmann; Barbosa, Claudio Clemente Faria
Abstract: The scarcity of long time-series of water temperature for tropical reservoirs, usually available at a low frequency of measurements, represents a serious constraint for the understanding of their thermal behavior. Hydrodynamic models become a powerful tool for that understanding through a qualitative approach. In this study, the one-dimensional General Lake Model (GLM) was applied to hindcast multiannual temperature profiles of a cascade system of six reservoirs located in southeast Brazil over a period of eight years. The model parameters were calibrated and validated by field data for four reservoirs. To overcome the challenge of exploring hydrodynamics in two reservoirs with a lack of measured temperatures, a parameterization strategy was applied to accomplish a better simulation by the estimation of potential sensitive parameters through regression curves. It is expected that this approach can be extended to other tropical reservoirs whenever field data is not available for the calibration procedure. Highlights: 1-D hydrodynamic simulation of a cascade of reservoirs in Tietê River (Brazil) is presented. Consistent sensitivity to surface heat exchange parameters in all reservoirs with available data. A parameterization strategy for a better prediction of surface heat exchange parameters in non-monitored reservoirs. Latent heat, sensible heat and momentum coefficients obtained from reservoir's mean depth, wind fetch and wind speed. Thermal behavior of six reservoirs is depicted from model results.